Series 1: The Use of hsp65- and erm(41)-Targeted Amplicon Sequencing in the Diagnostic Workflow for Non-Tuberculous Mycobacteria - Tracy Lee; Adriana Cabrera; Kathleen Kolehmainen; Trevor Hird; Danielle Jorgensen; Alan O’Dwyer; Dan Fornika; Rupinder Kaur KhunKhun; Mabel Rodrigues; Natalie Prystajecky; John Tyson; Inna Sekirov; et al. (Tropical Medicine and Infectious Disease)
Evolving technologies available to clinical laboratories and laboratory-related updates to clinical guidelines both drive the need for clinical laboratories to keep their test menu updated and in line with current technological and clinical developments. Our laboratory has developed a targeted Illumina-based amplicon next-generation sequencing (NGS) assay to interrogate the hsp65 and erm(41) genes of Mycobacterium spp. for the purposes of providing species-level ± subspecies-level identification of Mycobacterium spp. organisms in clinical samples and genotypic predictions for inducible macrolide resistance (in the case of M. abscessus complex members). The developed assay demonstrated 100% sensitivity and specificity for M. tuberculosis and M. abscessus complex cultured organisms, 98% ID overall concordance relative to the available reference identification, and a nearly 60% “rescue” rate for primary samples that could not be identified using our previous method. There was 94.6% concordance between genotypic and phenotypic results for inducible macrolide resistance. The developed assay was successfully implemented in our clinical laboratory and has been accredited for clinical use.